Rereading the Concept of Heterotopia: Buca Prison and Its Neighborhood - Yılmaz, Ebru; Öztürk, Duygu (Izmir Institute of Technology, 2022)
Since their conceptual existence, prisons have been spaces used by the power to separate individuals who are considered to be disrupting the structure of society from the society. Concepts that have differentiated with the sociological and cultural structures of societies that have changed over time have also evolved their own spatial systems in accordance with their own changes. French researcher Michel Foucault's researches and theories on prisons have contributed to making them not just physical spaces, making their interactions with their environments visible, and making them a tool that provides a clearer understanding of their role in the transformation of cities and societies inherent in power. The concept of Heteratopia, which Foucault mentions in his work on the Other Space, is a concept that should be evaluated together with the imposition form based on principles developed with physical rules and the tools used by the power to produce itself, emerging in the network of relations, regarding understanding how spaces produce information after the 20th century. Intersections that meet this concept in cities also benefit an active role with some physical boundaries or administrative forms operated by the power. Buca Prison, which has been visible for years on the busiest street of the city with its sharp borders, has become a structure where such spatial relations diversify, dominate and become visible. Buca prison, which has seriously affected the built environment in which it is located, has defined new spatial boundaries arising from social relations for years. When these spatial boundaries are evaluated within the scope of Foucault's studies, new responses and information are produced. For all these reasons, this study analyzes how Buca was affected by Buca Prison, using archive scans and qualitative research method ve evaluated the spatial sections associated with the city with theoretical approaches from the perspective of Foucault.

Cezaevleri kavramsal olarak var olmaya başladıkları zamandan bu yana, erkin, toplumun yapısını bozduğunu düşündüğü bireyleri, toplumdan ayırmak için kullandıkları alanlar olmuşlardır. Toplumların zamanla değişen sosyolojik ve kültürel yapıları ile farklılaşan kavramlar, kendi mekansal sistemlerini de, kendi değişimlerine uygun şekilde evrimleştirmişlerdir. Fransız araştırmacı, Michel Foucault’un cezaevleri ilgili yaptığı araştırmalar ve ortaya attığı teoriler, onları sadece fiziksel mekan olmaktan çıkartarak çevreleriyle etkileşimlerini görünür kılan, kentlerin ve toplumların iktidara içkin olan dönüşümündeki rollerinin daha net anlaşılmasını sağlayan birer araç haline gelmesine katkı sağlamıştır. Foucault’un Öteki Mekana dair adlı çalışmasında bahsettiği, Heteratopya kavramı, mekanların 20.yüzyıldan sonra nasıl bilgiler ürettiğinin anlaşılmasına ilişkin, ilişkiler ağında ortaya çıkan, fiziksel kurallarla geliştirilen prensiplere dayalı dayatma biçimi ve iktidarın kendini üretme şeklinde kullandığı araçlarla ile birlikte değerlendirilmesi gereken bir kavram olarak görülebilir. Kentlerdeki bu kavramı karşılayan ara kesitler, bazı fiziksel sınırlarla veya iktidarın işlettiği yönetimsel biçimlerle etkin bir rol de kazanmaktadır. Kentin en işlek caddesinde senelerce keskin sınırlarıyla görünür olan Buca Hapishanesi bu anlamda bu tür mekansal ilişkilerin çeşitlendiği, baskınlaştığı, görünür kıldığı bir yapı haline gelmiştir. Bulunduğu yapılı çevreyi ciddi şekilde etkilen Buca ceza evi senelerce toplumsal ilişkilerden de doğan yeni mekansal sınırlar tanımlamıştır. Bu mekansal sınırlar Foucault’un çalışmaları kapsamında değerlendirildiğinde ise yeni karşılıklar ve bilgiler üremektedir. Bütün bu sebeplerle, bu çalışma arşiv taramaları ve nitel araştırma yöntemi kullanarak Buca Cezaevi’nden Buca’nın nasıl etkilendiğini analiz ederek, kentle ilişkili mekansal kesitleri Foucault perspekifinden teorik yaklaşımlarla değerlendirmiştir.
Heterotopya Kavramını Yeniden Okumak: Buca Cezaevi ve Çevresi
Thesis (Master)--Izmir Institute of Technology, Architecture, Izmir, 2022
Includes bibliographical references (leaves. 108-119)
Text in English; Abstract: Turkish and English
Keywords: Buca Prison; Heteratopia; Neighborhood; Public spaces